Improved processing methods for eddy covariance measurements in calculating sensible heat fluxes at glacier surfaces - Cole Lord-May; Valentina Radić (Journal of Glaciology)
Bulk aerodynamic methods have been shown to perform poorly in computing turbulent heat fluxes at glacier surfaces during shallow katabatic winds. Katabatic surface layers have different wind shear and flux profiles to the surface layers for which the bulk methods were developed, potentially invalidating their use in these conditions. In addition, eddy covariance-derived turbulent heat fluxes are unlikely to be representative of surface conditions when eddy covariance data are collected close to the wind speed maximum (WSM). Here we utilize two months of eddy covariance and meteorological data measured at three different heights (1 m, 2 m, and 3 m) at Kaskawulsh Glacier in the Yukon, Canada, to re-examine the performance of bulk methods relative to eddy covariance-derived fluxes under different near-surface flow regimes. We propose a new set of processing methods for one-level eddy covariance data to ensure the validity of calculated fluxes during highly variable flows and low-level wind speed maxima, which leads to improved agreement between eddy covariance-derived and modelled fluxes across all flow regimes, with the best agreement (correlation >0.9) 1 m above the surface. Contrary to previous studies, these results show that adequately processed eddy covariance data collected at or above the WSM can provide valid estimates of surface heat fluxes.